Injury burden in professional European football (soccer): Systematic review, meta-analysis, and economic considerations - Pulici, L.; Certa, D.; Zago, M.; Volpi, P.; Esposito, F. (Clinical Journal of Sport Medicine, 2023)
Objective: We performed a systematic review and meta-analysis to evaluate the injury burden and the related economic cost in European professional male football players.